2020
DOI: 10.1128/aac.00198-20
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis of Reduced Susceptibility to Ceftazidime-Avibactam and Cefiderocol in Enterobacter cloacae Due to AmpC R2 Loop Deletion

Abstract: Ceftazidime-avibactam and cefiderocol are two of the latest generation β-lactam agents that possess expanded activity against highly drug-resistant bacteria, including carbapenem-resistant Enterobacterales. Here, we show that structural changes in AmpC β-lactamases can confer reduced susceptibility to both agents. A multidrug-resistant Enterobacter cloacae clinical strain (Ent385) was found to be resistant to ceftazidime-avibactam and cefiderocol without prior exposure to either agent. The AmpC β-lactamase of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 36 publications
2
36
0
Order By: Relevance
“…These deletions appear to broadly impact cephalosporin antibiotics in that they confer resistance to cefepime, CAZ-AVI, and cefiderocol—in the absence of preceding exposure to CAZ-AVI or cefiderocol. The same group described a third patient with an E. cloacae clinical isolate with a cefiderocol MIC of >16 mcg/mL with an alanine–proline deletion at positions 294 and 295 and a leucine-to-valine substitution at position 296 in AmpC [ 10 ]. Conformation changes in the R2 loop of AmpC β-lactamases expand its substrate binding site, enabling entrapment of cephalosporins with bulkier R2 side chains, increasing their hydrolysis [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These deletions appear to broadly impact cephalosporin antibiotics in that they confer resistance to cefepime, CAZ-AVI, and cefiderocol—in the absence of preceding exposure to CAZ-AVI or cefiderocol. The same group described a third patient with an E. cloacae clinical isolate with a cefiderocol MIC of >16 mcg/mL with an alanine–proline deletion at positions 294 and 295 and a leucine-to-valine substitution at position 296 in AmpC [ 10 ]. Conformation changes in the R2 loop of AmpC β-lactamases expand its substrate binding site, enabling entrapment of cephalosporins with bulkier R2 side chains, increasing their hydrolysis [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Before the clinical use of cefiderocol, there was widespread belief that resistance would primarily result from mutations in TonB-dependent receptors (TBDRs), a series of bacterial outer membrane proteins that mediate siderophore–iron complex transport [ 4-6 ]. While such mutations have been identified [ 7 , 8 ], there have also been isolated reports of changes in the ampC region contributing to cefiderocol resistance among the Enterobacterales [ 9 , 10 ]. This may occur after exposure to oxyminocephalosporins, such as CAZ-AVI or cefepime, in the absence of exposure to cefiderocol.…”
mentioning
confidence: 99%
“…(v) Distances and angles. PDB entries were the following: AmpC Ent385 -AVI ( 55 ) ( 6LC8 ), PDC-1-AVI ( 29 ) ( 4OOY ), PDC-1-REL ( 20 ) ( 4NK3 ), TRU-1-AVI ( 28 ) ( 6FM7 ), PDC-1-NAC ( 18 ) ( 4X68 ), and FOX-1-AVI ( 27 ) ( 5ZA2 ). In the structure of the AmpC Ent385 -AVI complex, K67 is observed in two conformations; in one it is not positioned to interact with N152 ( 55 ).…”
Section: Resultsmentioning
confidence: 99%
“…While neither resistance pattern to cefiderocol nor the underlying mechanisms have been studied, Kawai et al reported reduced susceptibility to cefiderocol in AmpC beta-lactamases with R2 loop deletion that increased hydrolysis of cefiderocol and ceftazidime-avibactam [ 19 ]. This finding explained the evolving survival strategy of MDR GNB to beta-lactam agents under selective pressure, and warrants further studies [ 19 ].…”
Section: Spectrum Of Activitymentioning
confidence: 99%